Cobia (Rachycentron canadum) hatchery-to-market aquaculture technology: recent advances at the University of Miami Experimental Hatchery (UMEH) - Benetti,Daniel (2010)
Among warm-water marine fishes, cobia is one of the best aquaculture candidate species in the world. Currently there are commercial culture operations in several Asian countries and the industry has started developing elsewhere, including the Western Central Atlantic region. Significant research has been conducted at the University of Miami's Aquaculture Program / University of Miami Experimental Hatchery (UMEH) during the last eight years, involving research to develop and optimize advanced technology to demonstrate the viability of raising hatchery-reared cobia in collaboration with the private sector. This paper reviews some of this recent advances for the development of Hatchery-to-Market Aquaculture Technology for commercial production of cobia.